Analysis of Nutritional Knowledge Levels among Hockey Athletes - Ahmad Ulul Bisri Husni; Shinta Masitho Windriyani; Mohammad Zaky Alfarezy (Sriwijaya Journal of Sport)
Research Problems: Athletes' nutritional knowledge can affect athlete performance both during training and matches. The situation in the field shows that many athletes still do not understand their nutritional needs, and irregular eating patterns so their performance in the field is less than optimal. This triggered researchers to examine further. Research Objectives: This study aims to determine the level of nutritional knowledge of Malang Regency hockey athletes. Methods: The type of research used is descriptive research, on the population of Malang Regency hockey athletes. The research sample of 57 athletes aged 16-18 years (M: 34, F: 23).  The research instrument used was a questionnaire.  Data analysis techniques used include percentage analysis of nutritional knowledge. Results: The level of nutritional knowledge of Malang Regency hockey athletes is 21% in the high category, 56% in the medium category and 23% in the lower category. Conclusion: The level of nutritional knowledge of Malang Regency hockey athletes is included in the moderate category. Researchers hope that many hockey athletes in Malang Regency have high nutritional knowledge. A very good level of athlete nutritional knowledge is expected to support athlete performance. Especially on a healthy diet. Healthy eating patterns can create healthy eating habits, both during training, matches and every day.